METODE PEMBELAJARAN DALAM AL-QUR'AN - Trisandi (Yayasan Pendidikan Islam dan Multikultural, 2022)
In essence, education is an effort to mature, namely to mature the minds of students to become more mature, independent, and have a more mature personality. Personality in question is all aspects of life which includes aspects of creativity, taste and intention. Education in a narrow sense is a learning process in schools (only a process of knowledge or cognitive transfer occurs), while in a broad sense it is a process of providing humans with various situations that aim to empower themselves. According to Law no. 20 of 2003 concerning the National Education System, education is a conscious, planned effort to create a learning atmosphere and learning process so that students can actively develop their potential.